PELAKSANAAN SERTIPIKASI MASSAL UKM DALAM UPAYA PENGEMBANGANYA DI KABUPATEN KUDUS - Nurdin Fuady Endang Sri Santi,Sri Sudaryatmi (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Land is very important for every individual in the society, because in addition to having a close relationship with the individual existence and survival in the environment, the land also has economic value. One cause of the problem is not registered all the existing plots of land so that the State can not guarantee the legal certainty of the rights of the public lands. This is in accordance with the provisions of Article 19 of the Basic Agrarian Law No.5 of 1960, which requires the Government of the Republic of Indonesia to host the Land Registry throughout the territory of the Republic of Indonesia the provisions stipulated in Government Regulation no. 24 of 2004 on Land Registration. The purpose of this research study is to determine in detail the implementation of UKM certificate programs in the Holy Land as well as the agency's office to find out the problems that arise and attempt to resolve the solution to a problem in the implementation process of land registration certificate program through mass. The method used in this paper is an empirical and systematic sociological juridical approach through primary data collection and secondary data. Data collection legal research that emphasizes the steps of observation and analysis conducted by interviewing informants whom the Holy District BPN Year 2011.Sedangkan secondary data obtained through the study of literature as well as legislation and literature. To draw conclusions from the results of research conducted by the method of qualitative analysis. Bulk certificate UKM Implementation Efforts Pengembanganya In less successful in the Holy District. Because the issues raised in the Holy ie no budget from the Government so that the implementation of the bulk UKM certificate has not been done.